Environmental impact assessment of steel and their alternatives in construction - Zheng, Yanlei (Nanyang Technological University, 2020)
Steel is one of the most conventional and used material in building construction today. Recently, there are multiple alternatives being proposed and used as a substitute for steel. Their suitability is evaluated through environmental implications. Whereas physical properties, and social and economic impacts are additional supporting factors that will be used to compare steel and its alternatives. Life Cycle Assessment (LCA) is an approach that takes into account of all the resources used and waste generated into the environment within an industrial system. LCA is a relative tool meant for comparison between alternative product or process, therefore assisting decision makers compare all categories of environmental impacts when deciding between different courses of action. In this study, the extensive research work will be carried out to compare the environmental impacts of steel and their alternatives from an environmental perspective. To assess if indeed these alternatives can one day be a substitute to the ever-rising use of Steel. LCA and assessing of the environmental impacts of steel and their alternatives used in the industry are performed by using ReCiPe Midpoint Method (H). The production process of the materials is researched and data such as materials consumed, waste generated and energy consumed under each process are collected as life cycle inventory. They are then input into ReCiPe Method where results based on 18 midpoint indicators also known as impact categories are generated. Ecoinvent database is also used to supplement the data as it offers well documented process data for array of products for modelling of each materials. From this study, results shown that steel have the highest impact indicator score across most of the impact categories than other materials. GFRP is ranked second, closely following behind Steel. Among 18 of the impact categories, climate change potentials, human toxicity potentials, ecotoxicity potentials and fossil depletion potential showed significant contributions to the high negative environmental impact scores of steel and GFRP. Bamboo scrimber displayed lower indicator scores as compared to both steel and GFRP. As for BFRP, the indicator scores for each of the impact categories are consistently low as compared to other materials as research have shown that environmental footprint of BFRP is almost 10 times less when compared to steel. Hence, BFRP is identified as a suitable alternative to steel followed by bamboo from an environmental perspective.